Percepções de estudantes de Ensino Médio sobre aprendizagem de inglês por meio de tarefa no Edmodo - Iurif, Vera Lúcia Nory Almansa (2016)
The objective of this research is to investigate the perceptions of a group of first year secondary school students from a São Paulo public state school about learning English language supported by Digital Information and Communication Technologies (DICT) resources, through a Task in the Virtual Learning Environment (VLE) Edmodo. This research is based on the perspective of the language learning as a social practice supported by the Orientações Curriculares Nacionais de Língua Estrangeira (BRASIL, 2006) and the Currículo do Estado de São Paulo: Linguagens, Códigos e suas Tecnologias - Ensino Fundamental II e Ensino Médio (SÃO PAULO, 2010). For this research, a Task was designed based on the communicative approach proposed by Willis (1996), and this Task was conducted through the VLE Edmodo, allowing interactions in a virtual environment and using DICT resources for learning English. This research was conducted in person, in a computer lab, with a group of thirteen first year secondary school students from a São Paulo public state school. The data gathering was done in the second semester of 2015, through four questionnaires and one interview. Regarding the students' learning process, the results reveal perceptions related not only to language knowledge improvement but also to digital knowledge improvement. Besides, the Task contributed to make the students aware of the possibilities of utilizing DICT for learning English in the school